2022
DOI: 10.2196/preprints.43636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive Bias Modification Training Targeting Fatigue in Patients With Kidney Disease: Usability Study (Preprint)

Abstract: BACKGROUND Fatigue is an important symptom for many patients, including kidney patients. Cognitive Bias Modification (CBM) training is a promising technique to counter fatigue symptoms. OBJECTIVE The current study aimed to evaluate a CBM training among kidney patients and health care professionals. Using an iterative design process, evaluating expectations and experiences with the training, acc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Both of these studies evaluated the application with multiple stakeholders (patients and health care professionals) and revealed positive results. Although in this usability study with people suffering from breast-cancer, preliminary data analyses only revealed a trend in altering self-identity bias (33), a pilot study with people suffering from chronic kidney disease revealed strong CBM effects on cognitive bias, and promising results on symptoms and related behaviour (34).…”
Section: Background Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Both of these studies evaluated the application with multiple stakeholders (patients and health care professionals) and revealed positive results. Although in this usability study with people suffering from breast-cancer, preliminary data analyses only revealed a trend in altering self-identity bias (33), a pilot study with people suffering from chronic kidney disease revealed strong CBM effects on cognitive bias, and promising results on symptoms and related behaviour (34).…”
Section: Background Introductionmentioning
confidence: 62%
“…This is also sent on Monday morning with a reminder on Wednesday morning. These procedures are inspired by a previous study with people suffering from chronic kidney disease (34).…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation